The Urge to Tell vs. the Need to Conceal: Confession as Narrative Desire in Poe’s “The Black Cat,” “The Tell-Tale Heart” and “The Imp of the Perverse” (American & British Studies Annual, 2014)
Relying on Peter Brooks’ concept of “narrative desire,” the paper seeks to identify and explore its applicability and manifestations in three of Edgar Allan Poe’s short stories: namely, “The Black Cat,” “The Tell-Tale Heart” and “The Imp of the Perverse.” Focusing on the role and nature of the narrators’ confessions in these three tales, this article seeks to show how the need or the urge to tell, constituting a recurrent preoccupation in Poe, may be further integrated within a framework of psychoanalytic criticism in which the emphasis is shifted from either the author or the text toward critical reading itself. As a result, the paper draws attention to the fundamental ambivalence permeating the construction of these texts, between telling and concealing. These contradictory tendencies are placed within Brooks’ theory of “textual energetics” and discussed in relation to his formulations on initiatory desire as well as the desire for the end, concepts which Brooks further connects to Freud’s model of instinctual drives in the form of Eros and Thanatos.
Keywords: E.A. Poe; short story; confession; murders; narrative desire; Peter Brooks; unconscious; ambivalence; instincts; psychoanalytic criticism